Fabrication of Amorphous Silver Nanowires by Helium Ion Beam Irradiation. (September 2015) - Shehla, H.; Ali, A.; Zongo, S.; Javed, I.; Ishaq, A.; Khizar, H.; Naseem, S.; Maaza, M.
Abstract : Amorphous silver nanowires (a-Ag NWs) are fabricated from crystalline Ag NWs by using 5 MeV helium (He + ) ion beam irradiation. At low dose (5 × 10 15 ion/cm 2 ), few defects are created in Ag NWs. As dose increases, more damage to the crystalline structure of Ag NWs is observed. Finally at high dose (8 × 10 16 ion/cm 2 ), the face-centered cubic structure of Ag NWs is transformed into the amorphous structure with similar morphology as Ag NWs. Phase transformation of crystalline Ag NWs upon irradiation with 5 MeV He + ions is observed through high resolution transmission electron microscopy. Synthesis of large scale amorphous metal nanowires and metal nanowire alloy systems are discussed.